EXPERIMENTAL STUDY OF MECHANICAL BEHAVIOR OF CHEMICALLY TREATED NATURAL SISAL FIBER REINFORCED CEMENTITIOUS COMPOSITE UNDER STATIC AND IMPACT LOADING - Sembiring, Suranta
Fiber Reinforced Cementitious Composite (FRCC) as a high-performance concrete material with constituent materials consisting of cement, pozzolanic materials (silica fume, fly ash, slag, etc.), fine aggregate, superplasticizer, water, and the use of fiber up to 2% volume fraction. The development and application of FRCC is still rare due to the use of synthetic fibers which are expensive, not available locally, and not environmentally friendly. The use of FRCC for structural and non-structural components in Indonesia is still very limited, so studies related to FRCC mixtures with natural fibers can still be developed further. This research focuses on the effect of fiber pre-treatment on morphology and tensile strength, mechanical characteristics of FRCC using natural fibers, viz. sisal fiber, both natural and modified sisal fibers, and other locally available materials under static and impact loads. Tests are carried out on fibers to evaluate the morphology and tensile strength of the fibers. Evaluation of the mechanical characteristics of FRCC against static loads, i.e. compressive strength, modulus and Poisson's ratio, flexural strength and tensile strength. Furthermore, an impact drop test was also carried out to evaluate the mechanical characteristics of the FRCC panel against impact loads, i.e the number of impacts until perforation, damage characteristics and failure mechanism, impact resistance, and punching shear analysis. From any pretreatments applied (thermal, NaOH, and Na2CO3), the most effective morphological changes and the most optimum in tensile strength increasing up to 37% were obtained by fibers that used chemical pre-treatment by a 10% Na2CO3 solution for 96 hours. The compressive strength obtained from non-fiber, untreated and chemically treated fiber FRCC cylinders is not significantly vary, by the range of 42.2-48.3 MPa. Compared to the non-fiber FRCC mixture, the average flexural strength of the FRCC of Untreated sisal fiber reached 3.66 MPa (increasing 31.7%) and the FRCC of Chemically Treated sisal fiber reached 3.78 MPa (increasing 41%). The average uniaxial tensile strength FRCC of Untreated sisal fiber reached 2.26 MPa (increasing 131%), while the FRCC tensile strength of Chemically Treated sisal fiber was 2.48 MPa (increasing 151%). Based on the results of impact tests on FRCC panels, the use of sisal fiber greatly improves the performance of FRCC resisted impact loads. Non-fiber FRCC panels with a thickness of 100 mm and 50 mm split immediately right after the first impact, while FRCC panels with a thickness of 100 mm with using natural and modified sisal fiber can resisted of 13 impacts and FRCC panels with a thickness of 50 mm with sisal fiber can resisted up to 4 impacts. The impact resistance energy that can be absorbed by Chemically Treated sisal fiber FRCC panels is 136.8 Nm, where there is an increase of 19.34% for panels with a thickness of 100 mm and 35.85% for panels with a thickness of 50 mm compared to FRCC panels with Untreated sisal fiber. The actual shear cone area on the 100 mm and 50 mm FRCC panels is similar with the empirical shear cone area according to the CEB-FIP 187-1998 model.